Curriculum 21 : essential education for a changing world - Jacobs, Heidi Hayes (Alexandria, VA : ASCD, 2010)
Contains articles that discuss ideas to improve and update the K-12 curriculum to prepare students for life in the twenty-first century, covering content and assessments, program structures, technology and media literacy, globalization, sustainability, and the thinking habits of students, teachers, and administrators.
A new essential curriculum for a new time / Heidi Hayes Jacobs -- Upgrading the curriculum : 21st century assessment types and skills / Heidi Hayes Jacobs -- Upgrading content : provocation, invigoration, and replacement / Heidi Hayes Jacobs -- New school versions : reinventing and reuniting school program structures / Heidi Hayes Jacobs -- Five socio-technology trends that change everything in learning and teaching / Stephen Wilmarth -- A classroom as wide as the world / Vivien Stewart -- Making learning irresistible : extending the journey of Mabry Middle School / Tim Tyson -- Media literacy : 21st century literacy skills / Frank W. Baker -- Digital portfolios and curriculum maps : linking teacher and student work / David Niguidula -- Educating for a sustainable future / Jaimie P. Cloud -- Power down or power up? / Alan November -- Creating learning connections with today's tech-savvy student / Bill Sheskey -- It takes some getting used to: rethinking curriculum for the 21st century / Arthur L. Costa and Bena Kallick.
Includes bibliographical references (p. 227-236) and index.
Professional
Keywords: Curriculum planning; Educational technology; Curriculum planning; Educational technology